WASTED OF YOUNG COCONUT SHELL AND SKINS AS AN ALTERNATIVE POLYBAG AND CHARCOAL BRICKET - Sibarani, Choms Gary Ganda Tua (Journal of Community Research and Service, 2022)
The community service activities carried out by the team on this occasion aim to provide several alternative side incomes for young coconut entrepreneurs. Some of the problems partners face in this regard are specifically in: a). Waste of young coconut shells and young coconut shells that are just thrown away and piled up beside/behind the young coconut business; b) the bookkeeping system is still traditional; there are even partners who did not record the books beforehand. Specific targets or solutions expected in this community service area). Partners can process young coconut waste into a new source of income, namely by making used coconut shells into natural and environmentally friendly pots/polybags by planting aglaonema flowers, and b). The scraps of peel and fragments of young coconut shell waste can be used as a fuel substitute for charcoal or briquettes. The service team handed over TTG in the form of closed burning barrels from used barrels for optimal combustion and simple financial training to determine the income from selling young coconuts to partners. Method of Implementation This service is carried out by carrying out the initial approach method, training, and mentoring on how to manufacture the finished product so that the alternative side income can be achieved maximally. The outputs produced in this activity are as follows: a) print and online mass media publications; (b) activity videos uploaded on youtube, and (c) articles in national journals with ISSN online and in print (d) trademarks (billboards/banners) creative designs, social media and also business location points on google maps.